Cumulus cell expansion, nuclear maturation and embryonic development of bovine cumulus-oocyte complexes matured in varying concentrations of follicular fluid - Verónica M. Negrón-Pérez; Abdullah Al Naib; Abigail L. Zezeski; Victoria L. McCracken-Harlow; George A. Perry; Alan D. Ealy; Michelle L. Rhoads (PLoS ONE, 2025)
In this study, we tested the overall hypothesis that CC expansion and early embryo development would be improved by including follicular fluid (FF) from small or large follicles in the oocyte maturation medium. In the first experiment, FF aspirated from bovine abattoir ovaries was added to the maturation medium at 0, 25, 50, 75 or 100%. Images of individual COCs were captured at 0, 6, 12 and 19 hours (h) of the maturation period and analyzed to calculate change in the total area over time. Cumulus cell expansion was greatest in COCs matured in 75% and 50% FF, and these differences were detectable at 12 (75% FF only) and 19 h (50% and 75% FF) of maturation. The improvement in CC expansion was greatest when FF from small follicles was used. Treatments for the subsequent experiments were selected based upon the results of the first experiment. Oocyte nuclear maturation rates were observed after supplementing the maturation medium with 0 or 75% FF and maturing for 19 h. The rate of nuclear maturation as determined by the presence or absence of the first polar body was similar between control (0% FF) and treated (75% FF) groups. In the final experiment, COCs were matured in 0%, 50% or 75% FF in preparation for IVF. Duration of the maturation period (12, 19 or 22 h) and size of the follicles from which FF was collected (small or large) also varied. In general, FF supplementation at 50% did not affect the zygotes’ developmental potential (neither increased nor decreased). Supplementation of maturation medium with 75% FF from small follicles consistently reduced measures of embryo development while 75% FF from large follicles yielded mixed results. It is concluded that FF supplementation improves CC expansion, but the greater CC expansion does not benefit subsequent embryo development. Notably, however, the 50% FF treatment did not reduce blastocyst rates, indicating that FF can be included in maturation media at concentrations of 50% or less with no detriment to IVF outcomes.